PENERAPAN LINGKUNGAN BAHASA ARAB DI ASRAMA PUTRI PESANTREN DARUL HADITS HUTABARINGIN DAN PROBLEMATIKANYA - Riski Salamah; Tauhid Tauhid; Isra Hayati Darman (STKIP Pesisir Selatan, 2026)
The purpose of implementing an Arabic language environment in the dormitory is to create a suitable atmosphere where female students in the dormitory use Arabic in their daily activities continuously. However, the implementation of the Arabic language environment in the girls' dormitory of Pesantren Darul Hadits Hutabaringin is not free from various problems and challenges. This study aims to determine how the Arabic language environment is implemented in the girls' dormitory, identify problems that hinder the implementation of the Arabic language environment in the girls' dormitory, and find out what efforts the teachers make to overcome the problems faced in implementing the Arabic language environment in the girls' dormitory of Pesantren Darul Hadits Hutabaringin. The results of this study are: the implementation of the Arabic language environment in the girls' dormitory of Pesantren Darul Hadits Hutabaringin through several programs, including the use of Arabic in daily activities, muhadatsah (conversation practice), muhadhoroh (lecture attendance), Mufrodat Al Yaumiyyah (daily vocabulary), learning nahwu and sharaf (Arabic grammar), as well as the giving of names or labels on rooms or objects in Arabic. Some problems that hinder the implementation of the Arabic language environment in the girls' dormitory include: declining motivation of the female students, their lack of ability in nahwu and sharaf, lack of interest in memorizing vocabulary, differences in the levels of Arabic proficiency among the students, weak supervision in the dormitory, influence of local languages, and limited adequate learning facilities.